Analisis Literasi Moderasi Beragama dalam Pembelajaran Aqidah Akhlak melalui Model Problem Based Learning (PBL) - Fahri, Muhammad Fahri; Nurman Ginting (PAI RAFAH, 2025)
This study aims to analyze religious moderation literacy in the Aqidah Akhlak subject through the Problem Based Learning (PBL) model at MTs Darul Ulum Budi Agung. The method used is a quasi-experimental design with a pretest-posttest control group. Data collection techniques included observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, consisting of three phases: data reduction, data presentation, and conclusion drawing. Observations described the implementation of the halaqah method as an effort to enhance students' religious moderation literacy. Data were collected through a religious moderation literacy test conducted before and after implementing the PBL model. The results showed a significant increase in religious moderation literacy in the experimental group compared to the control group. The average pretest score for the experimental group was 65, which increased to 85 in the posttest, while the control group only increased from 64 to 70. Data analysis confirmed the effectiveness of PBL in fostering students' engagement and critical thinking. Instrument validation showed high results in readability (89%), clarity (86%), content suitability (91%), practicality (87%), and reliability (0.86). The implementation of the PBL model proved effective in enhancing religious moderation literacy by encouraging active participation and critical thinking among students. These findings contribute to the development of instructional models in Aqidah Akhlak education by providing empirical evidence of PBL’s role in strengthening religious moderation literacy. Based on these findings, it is recommended that the PBL model be more widely implemented in Aqidah Akhlak education and other subjects related to character education and religious moderation.